Pengaruh Disiplin Kerja dan Lingkungan Kerja Terhadap Produktivitas Karyawan - Darmawan , Didit; Yahesa, Ayun Triska; Khofifah, Ilmia Nur (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Employee productivity is a strategic factor in maintaining organizational competitiveness in the era of globalization. Work discipline and a conducive work environment are two major factors that affect productivity. Work discipline reflects employee compliance, responsibility, and professionalism towards organizational rules, while the work environment includes physical, social, and psychological aspects that support comfort, motivation, and work concentration. This study aims to analyze the influence of work discipline and work environment on employee productivity through a qualitative approach. The literature review method was used to systematically collect and analyze previous research findings. Data were obtained from scientific articles in international and national databases such as Scopus, ProQuest, Google Scholar, and DOAJ, selected based on inclusion and exclusion criteria. The results of the analysis show that work discipline and work environment have a positive and significant contribution to productivity, complementing each other to improve efficiency, motivation, and quality of work results. These findings emphasize the importance of implementing managerial policies that emphasize strengthening discipline. In addition, creating a supportive work environment allows organizations to maintain a sustainable competitive advantage.